Hospital Discharge Within a Day After Total Knee Arthroplasty Does Not Affect 1-Year Complications Compared With Rapid Discharge. Issue 9 (1st May 2021) - Fassihi, Safa C.; Malahias, Michael-Alexander; Gu, Alex; Richardson, Shawn S.; Buller, Leonard T.; Stake, Seth; De Martino, Ivan; Pathak, Neil; Chen, Aaron Z.; Ast, Michael P.; Sculco, Peter K.
Abstract : Introduction: In patients undergoing total knee arthroplasty (TKA), it is unclear whether a difference in complication rates exists between patients discharged the day of surgery compared with subsequent postoperative days. Methods: Data were collected from the PearlDiver Patient Records Database from 2007 to 2017. Subjects were identified using International Classification of Diseases codes. Eligible patients were stratified into the following three groups: (1) same day discharge (<24 hours postoperatively), (2) rapid discharge (1 to 2 days), and (3) traditional discharge (3 to 4 days) based on the length of stay. Results: In total, 84, 864 patients were identified as having undergone primary TKA. The incidence of same day discharge, rapid discharge, and traditional discharge was 2.36% (2, 004/84, 864), 28.56% (24, 235/84, 864), and 69.08% (58, 625/84, 864), respectively. After adjustment, no notable differences were observed in the overall complication and revision rates between the same day discharge group and either the rapid discharge or the traditional discharge group. On multivariate analysis, patients in the rapid discharge cohort were less likely to require manipulation under anesthesia or develop periprosthetic joint infection when compared with the traditional discharge group at 1 year postoperatively. Conclusions: For those who qualify after careful selection, same day and rapid discharge TKA may be a feasible alternative to the traditional inpatient TKA. Level of Evidence: A level 3 retrospective, prognostic study